Employee ownership, corporate social responsibility and financial performance: evidence from the UK. (26th September 2022) - Orazayeva, Assem; Arslan, Muhammad
This study examines the impact of employee ownership on corporate social responsibility (CSR) and financial performance of 72 publicly listed UK firms for the period from 2011 to 2020. The objective of this study is to evaluate the magnitude and significance of the relationship. Prior literature presents limited evidence of the effects of employee ownership on social and financial aspects of firm performance, with focus on other ownership types. However, recent turbulent years caused by the global pandemic put employees as a stakeholder group under the spotlight, not only showing their importance but also vulnerability, thereby motivating this study to address employee-related issue. Contrary to the initial predictions of this study, we found small negative statistically significant coefficient between employee ownership and CSR. The link between CSR and financial performance was also observed to be negative, though the result lacks statistical significance. The study makes both theoretical and practical contributions by expanding current literature on employee ownership effects, as well as adding evidence for practitioners who consider changes in the ownership structure.